Millennial and Islamic Financial Products - Diyan Lestari (Institut Agama Islam Negeri Kendari, 2020)
Islamic financial products have quite different characteristic compare to conventional financial products, especially related to fundamental principle. Islamic finance should implement sharia law which consider Islamic rule in Quran and Hadist. The rise of Indonesian millennial awareness in Islamic products impact on how firms conduct their business, especially related to financial products because they are relatively complex. This paper attempts to provide an understanding related to millennial consideration in Islamic financial products which examine several aspects, such as Islamic financial literacy, Islamic lifestyle, perceive risk, and social influence. Smart PLS is used to analyze 600 data in order to provide statistical result. Purposive sampling is a technique that this paper used to classified research data. The finding indicates that all variables have strong relationship to determine Islamic financial products decision making. Most variables impact millennial behavior in using financial products, except perceive risk and social influence. The result of this study also provides practical implication for Islamic finance institution, government, academic, and business owner.